The Application of Substantive Justice in the Indonesian Criminal Code to Online Gambling Offenders Through the Principle of Proportionality in the Prosecution Process - Rolando Ritonga (Journal Customary Law, 2026)
The rapid development of digital technology has transformed gambling from a conventional offense into an online-based crime involving complex networks and cross-regional actors, while law enforcement in Indonesia continues to focus primarily on lower-level offenders, resulting in disparities in justice. This study aims to analyze the regulation of gambling offenses within the Indonesian criminal law system, examine current law enforcement practices against online gambling offenders, and explore the importance of applying the principle of proportionality in the prosecution process to achieve substantive justice. This research adopts a normative juridical approach with a descriptive-analytical method, utilizing library research on primary, secondary, and tertiary legal materials, which are analyzed qualitatively through legal interpretation, systematization, and argumentation. The findings indicate that although the legal framework has accommodated online gambling offenses, enforcement practices remain dominated by a retributive paradigm and have not optimally incorporated the principle of proportionality, resulting in an imbalance between the degree of culpability and the sanctions imposed. Furthermore, the socio-economic background of offenders has not been adequately considered in prosecutorial decision-making. This study contributes conceptually by proposing the integration of proportionality and substantive justice as a foundation for a more equitable, rational, and humane prosecution policy within the Indonesian criminal justice system.